Correlation between Glycemic Control in Type 2 Diabetes Mellitus Patients with Natural Killer Cell Activity - Ristanti, Dian; Soegiarto, Gatot; Novida, Hermina (UI Scholars Hub, 2019)
Introduction. Most of the previous studies showed decreased polymorphonuclear cells and monocytes/macrophages in type 2 diabetes mellitus (T2DM). Natural killer (NK) cell functions were rarely studied in T2DM. This study aimed to evaluate NK cell activity and determine its correlation with glycemic control in T2DM patients. Methods. Type 2 diabetes mellitus (T2DM) patients who regularly visit the diabetes outpatient clinic of Dr. Soetomo General Hospital during July – August 2018 and fulfill the inclusion-exclusion criteria were recruited to the study. The HbA1c level was measured according to the standard procedure. The NK cell activity was measured using flow cytometry and expressed as the percentage of activated NK cells from total NK cell numbers. Correlation between the two variables was determined. Results. There were 38 subjects eligible for this study, consisted of 15 males and 23 females, with mean of age 52 (standard deviation [SD] 6) years. The subjects routinely received OAD (36.8%), insulin (44.7%), or OAD-Insulin combination therapy (18.4%). Median HbA1c was 7.8% (range: 5.5 – 13%). Median NK cell activity was 7.08% (range: 2.95 – 21.55%). Using a Spearman test, there was no significant correlation between HbA1c levels and NK cell activity (r=0.292; p=0.075). Conclusions. The glycemic control in T2DM did not significantly influence NK cell activity. Further exploration and research should be done to determine whether there were changes in NK cells that contribute to innate immune dysfunction in T2DM patients.